Electron Beam Melting Fabrication of Porous Ti6Al4V Scaffolds: Cytocompatibility and Osteogenesis*. Issue 9 (11th March 2015) - Lv, Jia; Jia, Zhaojun; Li, Jing; Wang, Yanen; Yang, Jun; Xiu, Peng; Zhang, Ke; Cai, Hong; Liu, Zhongjun
<x xml:space="preserve">Abstract</x> Titanium‐based implants possessing adequately low elasticity modulus and customdesigned structures are urgently demanded in recent years for orthopedic applications. Electron beam melting (EBM) provides an opportunity to fabricated porous titanium scaffolds that meet the as‐mentioned requirements, and it further allows for improved bone regeneration and increased contact area at implant–tissue interface. As a novel additive manufacturing (AM) technique, EBM could conveniently produce scaffolds with tunable porosity and shapes and complex structures based on the popular "bottom‐up" concept. In the present work, EBM‐produced Ti6Al4V cylinders designed with either a small pore size (EBMS, 640 μm) or a large one (EBML, 1200 μm) were characterized in respect of microstructure, permeability and specific surface area, and their cytocompatibility and osteogenic ability were evaluated subsequently in vitro. Both samples EBMS and EBML could support the attachment and proliferation of hMSCs with minimal inflammatory cytokines secretion. The EBMS scaffolds were relatively more compatible with hMSCs than the EBML and they better sustained osteogenesis probably for their larger specific surface area.